Registration of 18 first cycle tropical midaltitude maize germplasm lines - Everett, L.; Eta-Ndu, J.T.; Ndioro, M.; Tabi, I.; Kim, S. (Wiley, 1994)
These germplasm lines (with PI numbers ranging from 550899 to PI550925) were released in 1991 for use as source germplasm or as parental lines in high-rainfall tropical midaltitude regions. They were developed by selfing in the IITA Midaltitude Streak Resistant (TZMSR) and tropical lowland (TZSRW) populations, and from these populations or derivative lines crossed with East African hybrids. The principal nursery and testing sites were in the Western and Adamawa Plateaux of Cameroon. Data on disease resistance was collected at 2 sites on the Jos Plateau of Nigeria and screening for maize streak monogeminivirus was conducted at Ibadan, Nigeria. Information is tabulated on the parentage, grain texture, days to silking, plant height and reaction to Exserohilum turcicum [Setosphaeria turcica], Cercospora zeae-maydis and Physoderma maydis of the germplasm lines. The lines are primarily late maturing and short in stature. All except one line have white grains and all are resistant or moderately resistant to MSV. They exhibit sufficient diversity of plant heights, maturities, grain types and disease resistance to contribute to a range of breeding requirements.